Self-microemulsifying drug-delivery system for improved oral bioavailability of 20(S)-25-methoxyl-dammarane-3β, 12β, 20-triol: preparation and evaluation - Cai S (Dove Medical Press, 2014)
Shuang Cai,1,* Cai-Hong Shi,2,* Xiangrong Zhang,2 Xiaojiao Tang,2 Hao Suo,2 Li Yang,2 Yuqing Zhao2 1Department of Pharmacy, The First Affiliated Hospital of China Medical University, 2Shenyang Pharmaceutical University, Shenyang, People's Republic of China *These authors contributed equally to this work Abstract: The objective of this study was to develop a self-microemulsifying drug delivery system (SMEDDS) to enhance the oral bioavailability of the poorly water-soluble compound 20(S)-25-methoxydammarane-3β;12β;20-triol (25-OCH3-PPD). Optimized SMEDDS formulations for 25-OCH3-PPD contained Cremophor® EL (50%) as the surfactant, glycerin (20%) as the cosurfactant, and Labrafil® M1944 (30%) as the oil. The SMEDDS were characterized by morphological observation and mean droplet size. The pharmacokinetics and bioavailability of the 25-OCH3-PPD suspension and SMEDDS were evaluated and compared in rats. The plasma concentrations of 25-OCH3-PPD and its main metabolite, 25-OH-PPD, were determined by ultra performance liquid chromatography-tandem mass spectrometry. The relative bioavailability of SMEDDS was dramatically enhanced by an average of 9.8-fold compared with the suspension. Improved solubility and lymphatic transport may contribute to this enhanced bioavailability. Our studies highlight the promise of SMEDDS for the delivery of 25-OCH3-PPD via the oral route. Keywords: 25-methoxydammarane-3β;12β;20-triol (25-OCH3-PPD), 25-OH-PPD, self-microemulsifying drug delivery system, bioavailability, pharmacokinetics